1988
DOI: 10.1177/089198878800100205
|View full text |Cite
|
Sign up to set email alerts
|

Memory Complaints and Memory Deficits in Young and Old Psychiatric Inpatients

Abstract: Memory complaints and memory deficits were investigated in 206 consecutively admitted psychiatric inpatients at the University of Iowa Psychiatric Hospital. Forty-five percent of patients over age 60 years and 29% of patients less than 60 years old had severe memory complaints. Patients with complaints of memory loss were no more likely than patients without such complaints to have a memory deficit. In patients over age 60 years, memory complaint was more common in depression than in dementing and amnestic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…did not identify which of the subdomains of the BDI are correlated with objective neuropsychological assessments 34 . In contrast to these results, some studies have shown that memory complaints are associated with depressive symptoms 35–37 but not with all domains of neuropsychological measurements, particularly psychomotor speed measures 38 . These inconsistent results may be due to the use of different symptom checklists or different subdomains in the different studies.…”
Section: Discussionmentioning
confidence: 84%
“…did not identify which of the subdomains of the BDI are correlated with objective neuropsychological assessments 34 . In contrast to these results, some studies have shown that memory complaints are associated with depressive symptoms 35–37 but not with all domains of neuropsychological measurements, particularly psychomotor speed measures 38 . These inconsistent results may be due to the use of different symptom checklists or different subdomains in the different studies.…”
Section: Discussionmentioning
confidence: 84%
“…Cognitive function, for example, is more often assessed by objective neuropsychological tests that quantify performance; however, the relationship between this performance and self-reported cognitive complaints is not well understood, as some data suggest a discrepancy between the two, [80][81][82] whereas other studies report some degree of consistency. [83,84] Unfortunately, many of these studies have focused predominantly on older individuals, with much less information available on younger depressed subjects. Sleep is another functional outcome that can be readily assessed by both self-report and objective measures.…”
Section: Self-reported Versus Objective Assessment Of Functional Impamentioning
confidence: 99%
“…Others have shown that memory complaint and impaired performance on objective psychological tests are poorly correlated (Sunderland et af., 1986;Derouesne et al, 1989;Rabbitt and Abson, 1990;Bolla et al 1991). One explanation for this discrepancy may be the presence of depression (Chandler and Gerndt, 1988;Bolla et al, 1991). Derouesne et al (1989) found that memory complaint was strongly correlated with self-reported depression even among those with low depression scores.…”
mentioning
confidence: 99%